치과위생사의 치매노인 구강건강관리 실태 및 인식에 관한 질적 연구 - 포커스 그룹 인터뷰 적용 - 정은서; Eun-seo Jung; 최윤영; Yoon-young Choi; 이경희; Kyeong-hee Lee (Han'guk Ch'iwisaeng Hakhoe chi, 2021)
Objectives: This study investigated the working conditions of dental hygienists and their challenges in providing oral care to older adults with dementia using focus group interviews. Methods: We collected data for approximately a month beginning from August 2020 and divided the study subjects into two groups: the health dental hygienist and the clinical dental hygienist groups. A total of 11 subjects participated in this study. Results: The oral health management of older adult patients with dementia has not been efficiently carried out in local communities or dental medical institutions. In addition, dental hygienists encounter difficulties in managing the oral health of these patients and hope to actively learn more about their special cases. Conclusions: Based on the results of this study, it is necessary to develop a manual or program for the professional implementation of oral health interventions for older adults with dementia.